Organización contable en la microempresa fantasías para ella & el de la ciudad de Yantzaza, período del 01 de octubre al 31 de diciembre del 2021. - Romero Samaniego, Silvia Beatriz (2022)
The present work of Curricular Integration called "ACCOUNTING ORGANIZATION IN THE MICROENTERPRISE FANTASÍAS PARA ELLA & EL DE LA CIUDAD DE YANTZAZA, PERIOD FROM OCTOBER 01 TO DECEMBER 31, 2021", was developed with the purpose of applying an accounting system to the microenterprise, according to the economic activity that it develops, to determine in a real and timely manner the economic-financial situation in which it finds itself, and to be able to provide a significant contribution to the owner, so that the necessary measures can be taken. better decisions for its growth and development. In order to comply with the first specific objective, the chart of accounts was drawn up, in which the proper distribution and classification of the accounts was established based on the needs of the microenterprise, thus facilitating management through coding, then the accounts manual was made, which basically represents the structure of the accounting system, which contains: coding, name of the account according to its nature, its description and the dynamics that each of them have. Also, to carry out the following objective, auxiliary records of purchases and sales were prepared, these allowed to detail in an orderly manner the transactions that are generated daily, in the same way the need was seen to make auxiliary annexes of accounts payable, where The purchases and payments made to the different suppliers were recorded, in the same way accounts receivable assistants were made to the clients, in which the payments canceled for the purchase of merchandise are detailed, then the payment roles were designed and monthly provisions, at the same time the respective depreciation and existing consumption are made. Finally, when carrying out the accounting process, the last objective set is fulfilled, which begins with the lifting of the Initial Inventory of all the values, assets, rights and obligations contracted by the microenterprise, which was carried out by verifying of the same, this in turn allowed to determine the Initial Inventory, where their assets, liabilities and equity are reflected, it was very useful to put together the Initial Situation Statement. Next, the owner provides the necessary information to prepare the memorandum of transactions, and thus be able to journalize the economic operations through the use of the multiple account system, in addition, the wholesale is carried out to obtain the balances of the checking balance, later for the preparation of the sheet of work, the values taken from the different adjustment entries are transferred and the Financial Statements are obtained. 5 In conclusion, the microenterprise presents during the months of October, November and December of the year 2021, a loss for the year, which is clearly reflected in the Income Statement, this due to the Health Emergency - Covid19 pandemic, around that sales fell significantly, making it difficult to have the same heyday of previous periods. Once the accounting process has been carried out, the conclusions and recommendations are drawn up, which will serve the owner of the microenterprise so that she can make the best decisions regarding the loss of the registered financial year.